Attitudes, Knowledge and Practices of Classroom Teachers and Physical Education Teachers to the Otherness and Culturally Relevant Pedagogy and Teaching - Aslanidou, Μαρία; Derri, Βασιλική (Inquiries in Physical Education and Sport, 2013)
Culturally relevant pedagogy and teaching aim at satisfying the academic and social needs of students from different cultural backgrounds. Therefore, the cultural competence of teachers in general and Educators of Physical Education (EPE) in particular is essential. The purpose of this study was a) to present the theoretical framework of cultural pedagogy and teaching, b) to investigate the attitudes of teachers in general and of EPE towards otherness, and their knowledge of the principles of culturally relevant pedagogy and teaching, c) to investigate the possibility of applying theory into practice, and d) to present culturally appropriate strategies that can be developed by teachers. The findings of the study indicated that the knowledge of teachers and their level of understanding towards the principles of culturally relevant pedagogy as well as their teaching practices are characterized incomplete and therefore need immediate change. Through the implementation of strategies and training, based on the principles of culturally relevant pedagogy and teaching, the knowledge and skills of teachers are expected to improve and consequently to satisfy the needs of all students.